Unfortunately last Sunday afternoon somebody left the door open ... - Esanu, Octavian; Huijts, Stijn; Schaerf, Eran; Jan Van Eyck Akademie, Maastricht (Sittard : Museum Het Domein, 2000)
Bouvy, Aline ; Bijl, Guillaume ; Cranston, Meg ; Dragnev, Lilia ; Gander, Ryan ; Gillis, John ; Gverovic, Tina ; Kinoshita, Suchan ; Konrad, Aglaia ; Kool, Renée ; Kroboth, Manfred ; Macari, Lucia ; Novikov, Timur ; Oorebeek, Willem ; Rata, Vasile ; Verlan, Mark ; Visch, Henk ; Zait, Nira
Engels
Unfortunately last Sunday afternoon somebody left the door open...., Museum Het Domein, Sittard, 27.06.2000 - 20.08.2000
boek